Expression of DNA methyltransferases is involved in Quercus suber cork quality - Ramos, Miguel; Rocheta, Margarida; Carvalho, Luísa; Inácio, Vera; Graça, José; Morais-Cecílio, Leonor (Tree Genetics & Genomes, 2013)
Abstract Cork oak (Quercus suber ) is an important Portuguese species, mainly due to the economic value of the cork it produces. Cork results from phellogen, a meristematic tissue, which can locally produce lenticels or have discontinu- ities, originating “defects”: pores and nail inclusions that are detrimental to cork industrial use. Epigenetic processes control plant development and its deregulation can lead to altered phenotypes; therefore, the study of epigenetic players in the phellogen is important to understand the emergence of cork's defects. DNA methyltransferases (DNMTs) and one protein associated to MET1 (DMAP1) were characterized in Q. suber, and their gene expression was analyzed in phellogen and con- tiguous differentiating cell layers of trees producing high and low quality cork, after the evaluation of their defects by physical and image analysis methods. All classes of DNMTs (MET, DRM, and CMT) with the respective canonical motifs were identified in Q. suber. The expression analyses of these genes showed that QsDRM2 was the most active methyltransferases in the cells analyzed, and that all the genes were differentially expressed in trees with distinct cork quality,with a tendency for higher expression levels in lowquality producers. Interestingly, the global methylation level was higher in cells with low expression of DNA methyltransferases. A positive and significant correlation was obtained between QsDMAP1 gene expression and the percentage of cork defects. This work provides the first evidence that cork quality in Q. suber is likely influenced by epigenetic mechanisms
Keywords: CMT3; Cork oak; Cork quality; DMAP1; DRM; MET1; MET2; phellogen activity

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.89310.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber